Komunikasi dan Kebudayaan Islam di Indonesia - Ahmad Yadi (UIN Sunan Kalijaga Yogyakarta, 2020)
This study tries to explore the link between communication and Islamic culture in Indonesia. To see the linkages, the authors used research with a library research method which focused three issues, namely first, the relationship between communication and culture; second, the relationship between culture and religion; and thirdly, the institutionalization of Islamic cultural values in Indonesia. The results of the study turned out that communication and culture are two things that are inseparable. If we talk about communication then we also talk about culture. Religion and culture are closely related and complementary such as the influence of Islam on culture and cultural influence on Islam. Therefore we know the term